KARAKTERISASI POPULASI PADI F4 HASIL PERSILANGAN INPAGO UNSOED 1 × BASMATI DELTA 9 - Dumaris Priskila Purba; Rayna Ligar Hasanah; Totok Agung Dwi Haryanto; Agus Suroto; Agus Riyanto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The performance of the cross-bred population in the F4 generation will confirm the plant breeding process, which is expected to approach the desired traits and understand how genetic traits are manifested in a population and their interactions with the environment. This research aimed to determine the performance of rice characteristics of F4 populations progeny from crossing of Inpago Unsoed 1 × Basmati Delta 9, and find out the closest relation, direct effect, indirect effect, and some characteristics of growth and yield. The experimental design used was a Randomized Block Design with Augmented Design treatment design with five blocks. The treatment tested in 150 rice genotypes of the F4 population progeny from crossing of Inpago Unsoed 1 × Basmati Delta 9 and 5 comparison varieties including Inpago Unsoed 1, Basmati Delta 9, Protani, Pro 20 Tangguh, and Inpari 31. The characters observed included plant height, flowering age, number of productive tillers, panicle length, harvest age, grain weight per clump, grain weight per panicle, number of grains per panicle, percentage of grain content per panicle, weight of 1000 seeds, rice length, and rice form. The yield showed that the performance of F4 population progeny from crossing of Inpago Unsoed 1 and Basmati Delta 9 was a population that was still segregated, indicated by the performance of F4 individuals who were higher than their parents, some were lower than their parents, and some were higher than one of their parents. Characters that correlate significantly and positively with yield include grain weight per panicle, number of grains per panicle, number of productive tillers, percentage of grain content, plant height, panicle length, and weight of 1000 seeds. The most closely related characters to yield and the highest direct effect are the grain weight per panicle and number of productive tillers, so that these characters can be used as an indicator selection in the next generation.